A Semiotic Analysis in Downy Collection Advertisement - Devi Santika; Verayanti Utami; Pratami, Nadya (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
In an advertisement there must be some verbal and visual signs are used. The signs also have certain meaning to deliver the message of the product or service.The study was conducted by observation method in order to obtain detail information. The method that used in analyzing this study is descriptive qualitative method. The analysis used the theory proposed by Saussure (1983:65) to analyze and described verbal and visual signs and to analyze the meaning of verbal and visual signs of the advertisements used theory from Barthes (1967) about the denotative and connotative meaning supported by theory of color by Wierzbicka (1996). Through the analysis the researcher found there are 72 data of verbal and visual signs divided into 38 connotative meanings and 34 denotative meanings. The denotative meaning in this research consists of the name of products, ingredients, also functions of each product. In the other hand, the connotative meaning consists of the statement in the advertisement, the color, the background,and also the model used in each advertisement that has hidden meaning.